Network of lies : the epic saga of Fox News, Donald Trump, and the battle for American democracy - Stelter, Brian (One Signal Publishers, Atria, 2023)
Featuring unbelievable behind-the-scenes details, the author, using his signature investigative prowess, exposes Fox News' blatant attempts to manipulate the truth, mislead the public and influence our elections, showing the insidious ways the media is damaging our democracy.